Quantifying CO2 Emissions and Energy Production from Power Plants to Run HVAC Systems in ASHRAE-Based Buildings - Odi Fawwaz Alrebei; Bushra Obeidat; Tamer Al-Radaideh; Laurent M. Le Page; Sally Hewlett; Anwar H. Al Assaf; Abdulkarem I. Amhamed (Energies, 2022)
Recent evidence available in the literature has highlighted that the high-energy consumption rate associated with air conditioning leads to the undesired “overcooling” condition in arid-climate regions. To this end, this study quantified the effects of increasing the cooling setpoint temperature on reducing energy consumption and CO2 emissions to mitigate overcooling. DesignBuilder software was used to simulate the performance of a generic building operating under the currently adopted ASHRAE HVAC criteria. It was found that increasing the cooling setpoint temperature by 1 °C will increase the operative temperature by approximately 0.25 °C and reduce the annual cooling electricity consumption required for each 1 m2 of an occupied area by approximately 8 kWh/year. This accounts for a reduction of 8% in cooling energy consumption compared to the ASHRAE cooling setpoint (i.e., t_s = 26 °C) and a reduction in the annual CO2 emission rate to roughly 4.8 kg/m2 °C. The largest reduction in cooling energy consumption and CO2 emissions was found to occur in October, with reduced rates of approximately–1.3 kWh/m2 °C and −0.8 kg/m2 °C, respectively.